The role of media and public relations departments in effective tourism marketing in sharjah - Alsalami, Wafa Khalfan Obaid Alghoul; Al-Zaman, Qamar (Linguistics and Culture Review, 2021)
The purpose of this paper is demonstrating the value of the public relations and media role in the industry of tourism and to justify its position. The research is survey depending and adopting a Sharjah case-study method by quantities approaches. It shows the growth of media activities and public relations within the tourism industry.